The Emprises of Gaia Hypothesis as Shown on the Film Maleficent - Lina Fadiyah; Livia Wulandari; Cahyaningsih Pujimahanani; Rommel Utungga Pasopati (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Maleficent (2014) is a Disney film that tells the story of a kind fairy named Maleficent. One day, several armies from the human kingdom invaded the forest and threatened the harmony of the land. Due to betrayal and loss of wings, Maleficent begins to build a kingdom of darkness to protect the fairy kingdom namely the Moors. The film indicates further ideas of relations between human and nature as also supported by Gaia Hypothesis. Then, how is Gaia Hypothesis represented on the Film Maleficent? By using a qualitative method, this paper describes the state of the kingdom in the fairy realm after humans tried to destroy it. Supported by the proposed Gaia Hypothesis by James Lovelock related to the relationship between women and nature, the ethics of caring, the idea of mother earth, and the idea of healing the earth. The results of this study concluded that there are still many people who want to destroy nature for their own sake. While there are other creatures that live there, guarding nature with all human’s might and empowered from this analysis can awaken human beings in the future to always keep nature alive for all creatures on earth.